Peran Pembimbing Kemasyarakatan dalam Pelaksanaan Pendampingan Anak di Wilayah Kerja Balai Pemasyarakatan Kelas II Bogor - Sulistyowati, R. Ayu Dwi (Universitas Halu Oleo, 2021)
The probation officers have a significant role in the system of juvenile criminal justice in Indonesia. They have a crucial role in the process of pre-adjudication, adjudication, and post-adjudication. This paper analyzes the role of probation officers in actualizing their role as juvenile facilitators, according to Law No. 11 of 2012 in the Probation Office of Class II of Bogor. This research applied a normative-law method by analyzing the secondary data from positive law related to the implementation of juvenile facilitation. The data were analyzed employing a qualitative law approach. This study finds that the performance of juvenile facilitation by the probation officer has not been optimum because the roles have been ignored and considered as not essential by the investigator, prosecutor, and judge.